Ревизия рода ковалевскиелла — Kowalewskiella Baczynska, 1914 (Cestoda, Cyclophyllidea). Сообщение I - Корнюшин, В.В. (Вестник зоологии, 1969)
As a result of revision of genus Kowalewskiella Baez,ynska, 1914, three species remain in it: K. longiannulata Baszynska, 1914, K- cingulifera (Krabbe, 1869), K. stagnatilidis (Burt, 1940). Representatives of two species, K. glareolae (Burt, 1940) and K. tringae (Cholodkovsky, 1913), apparently belong to one of the three above mentioned species, but poor description of them make them temporarily independent. The species K. hypoleucia (Singh, 1952) is considered as synonym to K. stagnatilidis, and K. totani Self et Janovi, 1965 unite with X. longiannulata. Four species are returned to the genus: created for them before Onderstepoortia О r 11 e p p, 1938, and Tubanguella Yamaguti, 1959. A new diagnosis of the genus Kowalewskiella is suggested, and the determinative table of species is presented.